Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/diagnostics12071544
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Diagnostic Performance by Adding Methylation Marker to Conventional Visual Examination in Identifying Oral Cancer

Abstract: Background: Visual oral examination (VOE) is a conventional oral cancer screening method. This study aimed to evaluate the value of methylation marker to assist VOE in identifying oral epithelial dysplasia and oral squamous cell carcinoma (OED/OSCC) from non-cancerous lesions in a real-world situation. Methods: 201 patients with high-risk personal habits who self-perceived oral anomaly were VOE examined, ZNF582 methylation (ZNF582m) tested, and histologically diagnosed. Results: Among them, 132 patients (65.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…After adjustment for all factors using the Cox proportional hazards model, the adjusted hazard ratio of malignant transformation for ZNF582 hypermethylation was 11.41 (95% CI, 2.05–63.66; p = 0.005), suggesting that ZNF582 methylation is an effective and noninvasive biomarker for identifying oral lesions with a high potential for malignant transformation [ 50 ]. An independent retrospective study comprising 132 patients with OPMD or oral cancer and 69 control subjects concluded that the performance of the ZNF582 methylation assay was equivalent to that of an experienced oral maxillofacial surgeon and thus can serve as a useful diagnostic to increase the efficacy in identifying oral malignant lesions [ 51 ].…”
Section: Noninvasive Epigenetic Biomarkers For Early Detection Of Hea...mentioning
confidence: 99%
See 1 more Smart Citation
“…After adjustment for all factors using the Cox proportional hazards model, the adjusted hazard ratio of malignant transformation for ZNF582 hypermethylation was 11.41 (95% CI, 2.05–63.66; p = 0.005), suggesting that ZNF582 methylation is an effective and noninvasive biomarker for identifying oral lesions with a high potential for malignant transformation [ 50 ]. An independent retrospective study comprising 132 patients with OPMD or oral cancer and 69 control subjects concluded that the performance of the ZNF582 methylation assay was equivalent to that of an experienced oral maxillofacial surgeon and thus can serve as a useful diagnostic to increase the efficacy in identifying oral malignant lesions [ 51 ].…”
Section: Noninvasive Epigenetic Biomarkers For Early Detection Of Hea...mentioning
confidence: 99%
“…Similarly, we can incorporate previously documented epigenetically altered gene clusters from head and neck cancer tissues ( Figure 4 ) into the mutational landscape of OPMD and distilled significant genes for validation assays. We have witnessed the success of implementing four methylated promoters for early-stage NPC diagnosis from plasma DNA samples (220 patients and 50 controls, ref [ 69 ]) and the predictive capability of ZNF582 m in OPMD malignant transformation from oral swab samples (171 patients with matched OPMD and normal mucosa in ref [ 50 ]; 201 patients in ref [ 51 ]). Therefore, it is highly likely that the approaches proposed above will lead to the discovery of even more effective epigenetic biomarkers that are clinically applicable.…”
Section: Future Directionsmentioning
confidence: 99%
“… 10 Therefore, as with cancers at other sites, detection of OC at an early stage is desirable, and referring patients to a core hospital and beginning treatment as early as possible are essential. 11 , 12 , 13 , 14…”
Section: Introductionmentioning
confidence: 99%
“…New effective examination and imaging techniques are being developed that allow the surgeon to better visualize the boundaries of the primary tumor before and during the surgery more precisely [12][13][14][15][16][17][18][19][20][21][22][23][24]. With the help of these techniques, it is possible, among other things, to have a positive impact on margin surveillance.…”
Section: Introductionmentioning
confidence: 99%